Buckling of Circular Cylinder under Axial Load - Chauhan, Sandeep; Ahmad, Azad (International Journal of Engineering and Technology, 2018)
Present investigation is initiated to understand the effects of axially applied load upon the buckling behavior of thin circular cylindrical shells. In this study circular cylinder of finite length is taken as variable along with thickness of the cylinder to improve the understanding of buckling behavior. Buckling load is determined by FEM analysis carried out through ABAQUS software. Results shows that as length of the cylinder increases, buckling load decreases while keeping diameter /thickness ratio constant. Results also reveals that buckling load increases as the diameter / thickness ratio decreases while length of the cylinder kept constant.Â